Comparative Analysis of Criminal Laws on Money Laundering in ASEAN Countries: Between Justice and Protection - Saida Flora, Henny; Syah, Kaharuddin; Erwin, Erwin; Avivi Nur Laila, Siti; Devi Lawra, Rifqi (UNES Law Review, 2024)
Globalization brings many conveniences to the activities of the community through technological advances. Globalization also makes the borders and distances between countries invisible, so that countries in the world can be connected to one another. On the other hand, globalization has a negative impact on the world, namely the emergence of transnational crimes. One of the transnational crimes that plague different countries is money laundering. It is the act of processing the proceeds of criminal activity with the intent of concealing the source of the criminal activity or transforming the profits of criminal activity or corruption into ostensibly legal assets. Money laundering has become a transnational crime that is complicated and difficult to solve in various countries around the world. In this journal, the author uses a legal approach and comparative law method to compare the regulation of money laundering in Indonesia, Singapore and the Philippines. The results of this study will be an examination of the development of money laundering in the era of globalization and the regulation of money laundering in Indonesia, Malaysia, Singapore and the Philippines.